Tonicity-responsive enhancer-binding protein promotes hepatocellular carcinogenesis, recurrence and metastasis. Issue 2 (2nd February 2018) - Lee, Jun Ho; Suh, Jae Hee; Choi, Soo Youn; Kang, Hyun Je; Lee, Hwan Hee; Ye, Byeong Jin; Lee, Gap Ryol; Jung, Seok Won; Kim, Chang Jae; Lee-Kwon, Whaseon; Park, Jiyoung; Myung, Kyungjae; et al.
Abstract : Objectives: Hepatocellular carcinoma (HCC) is a common cancer with high rate of recurrence and mortality. Diverse aetiological agents and wide heterogeneity in individual tumours impede effective and personalised treatment. Tonicity-responsive enhancer-binding protein (TonEBP) is a transcriptional cofactor for the expression of proinflammatory genes. Although inflammation is intimately associated with the pathogenesis of HCC, the role of TonEBP is unknown. We aimed to identify function of TonEBP in HCC. Design: Tumours with surrounding hepatic tissues were obtained from 296 patients with HCC who received completion resection. TonEBP expression was analysed by quantitative reverse transcription–quantitative real-time PCR (RT-PCR) and immunohfistochemical analyses of tissue microarrays. Mice with TonEBP haplodeficiency, and hepatocyte-specific and myeloid-specific TonEBP deletion were used along with HCC and hepatocyte cell lines. Results: TonEBP expression is higher in tumours than in adjacent non-tumour tissues in 92.6% of patients with HCC regardless of aetiology associated. The TonEBP expression in tumours and adjacent non-tumour tissues predicts recurrence, metastasis and death in multivariate analyses. TonEBP drives the expression of cyclo-oxygenase-2 (COX-2) by stimulating the promoter. In mouse models of HCC, three common sites of TonEBP action in response to diverse aetiological agents leading to tumourigenesis and tumour growth were found: cell injury and inflammation, induction by oxidative stress and stimulation of the COX-2 promoter. Conclusions: TonEBP is a key component of the common pathway in tumourigenesis and tumour progression of HCC in response to diverse aetiological insults. TonEBP is involved in multiple steps along the pathway, rendering it an attractive therapeutic target as well as a prognostic biomarker.